Psychological Factors Faced By Junior High School Students In Learning English - Pipit Lionita Putri (Indonesian Journal of Education Research (IJoER), 2020)
Purpose of the study: The purpose of the research was to find out psychological factors faced by students in learning English and to know dominant factor in psychological factor affected students in learning English at the first grade of SMP N 30 Muaro Jambi. Methodology: This reseach used quantitative reseach. The data were collected through close ended questionnaire with 59 statements. There were 69 students with 38 male and 31 female students in Smp N 30 Muaro Jambi participated as the sample of this reseach. The data were analyzed by using frequency and percentage of the participant’s choices and drawn the conclusion based on sub-variables in specification of the questionnaire. There were six psychological factors included in this research they are (motivation, anxiety, self-esteem, attention, cognitive readiness and intelligence). Main Findings: Based on the result in this research all factors from psychological factors show the highest avarage scores (strongly agree and agree). Its means that psychological factor could affect learners to study foreign language and of course psychological factors affected students when they learn English in classroom. Because psychological factors were playing a crucial part in the process of learning. Novelty/Originality of this study: Psychological factors which have been widely acknowledge by the researchers could be viewed as an important element in assessing students academic failure especially attention because attention was one of the important things in learning process